Emergency surgery for acute cholecystitis caused by cholecystocolonic fistula - Vera-Portilla, Angel F. (2021)
Cholecystocolonic fistula (CCF) is a rare complication of cholelithiasis. They are often asymptomatic, difficult to diagnose preoperatively, it despite radiological support, and they are discovered incidentally perioperatively. We present the case of a woman with acute cholecystitis, who was operated by laparoscopy, and a CCF was evidenced, it was resolved by conversion to open surgery. FCC can be complicated and simulate acute abdominal symptoms. It should be taken into account in older adults with a history of cholelithiasis and scleroatrophic vesicles with adhesions. Very few cases have been described in the literature, and none in our country. We present a case of FCC that was admitted as acute cholecystitis, and the diagnosis and treatment of it were during her surgery.